Micro strip feed monopole circle to circle fractal antenna for multiband applications - Yogaprasad, K; V. R Anitha, Dr (International Journal of Engineering and Technology, 2018)
In this paper, introduced monopole circle to circle fractal based antenna for multiband applications fed by microstrip line. The FR-4 substrate and copper material used in this proposed design. This is operated in between the 6-20GHz frequency band and achieves 8 resonant frequencies and also used for C/X/Ku/K band applications i.e., multiband applications. The Computer simu-lation technology software is used for design and discussed the general results of antenna-like reflection coefficient, VSWR, Gain, Radiation Pattern and efficiencies and dimensions of a proposed structure is 26mm x30mm x1.6mm.Â Â